Upaya Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X Melalui Pembelajaran Kooperatif Tipe Numbered Head Together - Khairani, Khairani; Amry, Zul; Harahap, Roslinawati (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
Critical thinking is reasonable reflective thinking focused on deciding what to believe or do. The upper three levels of Bloomâs taxonomy of educational objectives (analysis, synthesis, and evaluation) are part of critical thinking. Purpose of this research was to improve critical thinking of tenth grade secondary students through Cooperative Learning Number Head Together (NHT). Type of this research was classroom action research. Subjects were 40 students of class X-6 MAN 2 Model Medan in year academic 2013/2014. This research had two cycles with three strategies to collecting data: experiencing, enquiring and examining. Researcher reflected studentsâ critical thinking through observation, test, interviews, and studentsâ records, before Cooperative Learning Numbered Head Together (NHT) is adopted in classroom. Data analysis was done by quantitative and qualitative approach. Based on data analysis, it shows that studentsâ critical thinking are increase from score percentage 32,42% at low level (before cyclus I) to 49,13% at medium level (after cyclus I) and 55,63% at medium level (after cyslus II). It can be concluded that studentsâ critical thinking can be improved by implementing cooperative learning numbered head together in the classroom.